Box americana - Antell, Benjamin; Lax, Patrick; Rintanen, Mikko, 1958- (2000)
12 kappaletta.
Box Americana ; I'm just coming 4 your love ; B my doctor yeah ; 2morrow could b yesterday ; Many a night ; Hollywood Pollywould SOAR ; If u would still b loving me ; My Billabong ; God in my garage II ; Sister Circumstance ; My darling daughter ; Departure.
Benjamin Antell (lauluääni, kitara, kosketinsoittimet, sähköurut, lyömäsoittimet, sitār, harppu, ohjelmointi, yhtye), Mikko Rintanen (kosketinsoittimet, kitara), Patrick Lax (rummut, lyömäsoittimet). - Ym. Esittäjäluettelo (myös teoskohtaisesti) tekstilehtisessä.
[Äänite]
Keywords: Antell, Benjamin -- albumit